Does the employment effect of National Minimum Wage vary by non-employment rate? A Regression Discontinuity approach - Lei Xu; Yu Zhu (Global Labor Organization (GLO), 2022)
We examine the impact of increasing minimum wage on employment by exploiting variation in the age-dependent National Minimum Wage (NMW) in the UK. We extend the Regression Discontinuity model to evaluate the procyclicality of employment effect and show that previous estimates may be biased due to failure to account for the local non-employment rate. Contrary to the existing literature, we report a positive employment elasticity after accounting for the effect of local labour market conditions. The results suggest that the positive employment effect of increasing minimum wage is strongly procyclical, i.e. is more pronounced in areas with low non-employment rates. Under an assumption that employers have no direct impact around the cut-off point, the results suggest that a higher minimum wage increases labour supply of young workers.
Keywords: J22; 330; minimum wage; macroeconomic fluctuation; regression discontinuity; age dependent; procyclicality